Outdoor Education: How Steiner Students view their outdoor sessions. - Wales, Emma (My University, 2019)
This thesis explores how Steiner students view their outdoor education sessions. The literature review explores outdoor education and provides an overview of Steiner education. Furthermore, photovoice is explored as a qualitative data collection method which is the use of visual images to share the voice of the participants. In addition to photovoice, the research uses short observations and poster presentations as data collection methods. This study attempts to gain an understanding of how Steiner students view their outdoor sessions with the aim of using a Grade 4 class as co researchers. By better understanding the students view and listening to the voice of the child, this thesis aims to provide teachers with a clearer understanding of the main aspects seen by children during outdoor sessions. The results indicated that there were four main themes that the students viewed during the outdoor sessions: place attachment, detail, social and forest setting.
Keywords: outdoor education, co researchers, Steiner education, photovoice, voice of the child, place attachment, visual images, school, Grade 4.